Influência do pH e carbono inorgânico na competição entre as cianobactérias Cylindrospermopsis raciborskii e Microcystis aeruginosa - BRITO, Maiara Tábatha da Silva (2017)
Cyanobacterial bloom in freshwater are mainly associated with the nutritional enrichment of the water, but currently, high concentration of atmospheric carbon dioxide (CO2) is also favoring its dominance. During bloom, the consumption of free CO2 and nutrients increases the pH of the water. Thus, when it diffuses in water, atmospheric CO2 becomes available as bicarbonate (HCO3-) and carbonate (CO32-), promoting changes in the phytoplankton community due to the competitive advantage that some species present in use of HCO3-. Cylindrospermopsis raciborskii and Microcystis aeruginosa are cyanobacteria widely distributed in freshwater aquatic ecosystems, bloom forming and known to make use of HCO3-. This study was carried out in order to investigate the competitive relationship between these species due to changes in pH and availability of inorganic carbon. Were performed cultures with and without aeration, with and without bicarbonate and in three different pH conditions (free, 6.8 and 8.2) with the strains ITEP-A1 of C. raciborskii and NPLJ4 of M. aeruginosa. Cultures started with the same biovolume and had their exponential growth phase extended from reinoculation into new culture medium (returning to the initial biovolume). For the mixed cultures the species with the lowest growth was considered. The growth rates (μ.day -1) and species yield, pH, alkalinity and inorganic carbon of the cultures were evaluated by repeated measures ANOVA. Isolate M. aeruginosa presented higher growth rates at pH 8.2 and free, and reduced growth at pH 6.8 while C. raciborskii was not influenced by pH. Both species promoted significant changes in pH in the non-buffered cultures (free pH). Aeration and bicarbonate were determinant factors for the response of the species in the competition cultures. In non-buffered cultures, with aeration and without addition of bicarbonate C. raciborskii was better competitor than M. aeruginosa, whereas this was best competitor in the cultures without aeration and with addition of bicarbonate. It was possible to observe changes in the competitive responses of the species to changes in pH and alkalinity and, consequently, to the proportions of dissolved inorganic carbon. Thus, with increased eutrophication of aquatic ecosystems associated with increased alkalinity and pH, changes in the competitive relationships of species are likely to occur, since the relief of inorganic carbon limitation may favor the dominance of potentially toxic cyanobacteria such as those of the genus Microcystis.